Dos currais da Trancham à “pequena notável”: interesses, oposições e utopias nos primeiros tempos da Universidade Federal de São Carlos – UFSCar - Moretti, Diego Profiti (Universidade Federal de São Carlos, 2020)
This work sought to rescue important aspects of the history of the Federal University of São Carlos, Brazil, located in time even before its effective installation, which occurred only in March 1970. Created from articles 11, 12 and 13 of Brazilian Federal Law 3,835 of 1960, UFSCar would only be installed in 1968, after a series of setbacks that, for many times, almost prevented its effective existence. Throughout its history, however, the University has paid little attention to the preservation of its institutional memory and the recording of the history of the people who have passed through it. In view of this reality, we seek to carry out, within the scope of chapter 1 of this work, a survey of the few official initiatives of historical preservation or relevant personal initiatives that have solidified as fundamental for the creation, in recent years, of a Multidisciplinary Unit of Memory and Historical Archives (UMMA), the first concrete initiative to promote an effective system for creating, processing, and making available historical collections at the University. Then, within the scope of chapter 2, we proposed to create a chronological narrative, after research of various sources, of the events that resulted in the legal foundation of UFSCar. In the eight-year gap between the first legal instrument to cite the institution and the effective creation of the Federal University of São Carlos Foundation, a series of political and academic oppositions proved to be obstacles to the original project. To better understand such oppositions, it was necessary, first, to know the existing environment and the people involved, which is appropriate to the Marxist dialectical method that guided our investigation. Thus, after a summary of the conditions of Brazilian education, from the “nation discovery” to the 1960s, we proceeded to an investigation into the public lives of Ernesto Pereira Lopes and Lauro Monteiro da Cruz, the so “parents” of the project of a Federal University in São Carlos. Having known his probable interests, we started to investigate the opposition to the project, first, from the University of São Paulo, which did not want to add to the new academic initiative its already well-established School of Engineering of São Carlos (EESC). Another opposition, this one of a highly political nature, was created thanks to the actions of Jânio Quadros, then President of Brazil, who proposed the total cancellation of the project, which, however, was reversed by actions of Pereira Lopes and Lauro Cruz within the scope of the National Congress. A third opposition, different from the others, sought not to destroy the University, as the previous intentions did, but to profoundly alter its design and form, taking to the capital of the State of São Paulo the legal structure set up for the first federal university in its boundaries, transforming the São Paulo School of Medicine (EPM) effectively in the new university institution. Those oppositions having been overcome, largely due to Pereira Lopes' insistent will and the parliamentary performance of Lauro Cruz. After this, we proceeded to an analysis of the historical elements related to obtaining the Trancham Farm to become the headquarters of the institution's São Carlos campus. Thus, we make a historical account of the university's first days, even before its effective institutionalization, seeking to assist in the efforts to preserve UFSCar's own memory.
From the stables of Trancham Farm to a “small remarkable”: interests, oppositions, and utopias at the beginning times of the Federal University of São Carlos, Brazil – UFSCar
De los estables de la Granja Trancham a la “pequeña notable”: intereses, oposiciones y utopías en los primeros años de la Universidad Federal de São Carlos, Brasil – UFSCar
Keywords: História da Universidade Federal de São Carlos (UFSCar); História da Educação Superior no Brasil; História de Instituições Escolares; History of the Federal University of São Carlos (UFSCar); History of Brazilian Higher Education; History of Educational Institutions; CIENCIAS HUMANAS::EDUCACAO::FUNDAMENTOS DA EDUCACAO; CIENCIAS HUMANAS::EDUCACAO::FUNDAMENTOS DA EDUCACAO::HISTORIA DA EDUCACAO; CIENCIAS HUMANAS::HISTORIA::HISTORIA DO BRASIL::HISTORIA REGIONAL DO BRASIL